THE ROLE OF ISLAMIC EDUCATION TEACHERS OF EARLY AGE IN THE ERADICATION OF ILLITERACY IN INDONESIA - Mahfud, Choirul (Institut Agama Islam Yasni Bungo, 2018)
Teachers are educational heroes. Progressive retreat of educational practices in a country is also determined by the role of the teacher. In this context, it is necessary and important to evaluate and discuss further how the portrait of reality (das sollen) and ideality (das sein) concerning teachers of Islamic religious education of early age in Indonesia. Therefore, this study focuses on the teacher's problem between ideality and reality. This study was written using qualitative data that derived from references and literature books, news, journals and opinions in mass media and other relevant sources in this study. This research focuses on the following important questions: Firstly, what and how is the role of early Islamic education teacher in literacy eradication in Indonesia? Second, how are the supporting factors and obstacles to the role of early Islamic education teachers in literacy eradication in Indonesia? Thirdly, what are the solutions and policy recommendations on the role of Islamic education teachers in literacy eradication in Indonesia? Keywords: PAI Teachers, Illiteracy, Ideality and Reality